Алгоритмы эффективного управления электроприводом - Козярук, Анатолий Евтихиевич (НТУ "ХПИ", 2010)
In the article are considered principles of the organization and algorithms of efficient control by electric drive of mechanisms with hard operation conditions.
Keywords: система электромеханическая; энергосбережение; система логического управления; система автоматизированного управления